2009
DOI: 10.1097/pas.0b013e31817d7ff4
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric Gland Adenoma

Abstract: Pyloric gland adenoma (PGA) is a rare neoplasm demonstrating gastric epithelial differentiation. In this series, we studied 41 PGAs from 36 patients. We compared them to 28 gastric foveolar type gastric adenomas (GTAs) from 25 patients. PGAs occurred in an older population with a mean age of 73 compared with 48 in GTAs (P<0.001). There was a significant female predominance, particularly for gastric PGAs. Morphologically, PGAs were characterized by closely packed pyloric gland-type tubules with a monolayer of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(56 citation statements)
references
References 13 publications
4
51
1
Order By: Relevance
“…Moreover, most gastric cancers in LS patients were of gastric mucin phenotype. Given that PGA is a gastric-type adenoma,21 our findings also support PGA as one of the precursor lesions of gastric cancer in LS.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, most gastric cancers in LS patients were of gastric mucin phenotype. Given that PGA is a gastric-type adenoma,21 our findings also support PGA as one of the precursor lesions of gastric cancer in LS.…”
Section: Discussionsupporting
confidence: 74%
“…PGA is an uncommon histologic subtype of gastric polyps. Until recently, it was not well established as a distinct entity, especially in the literature from the United States 21,23. PGA occurs more commonly in older women and predominantly in the cardia and fundic mucosa in H. pylori or autoimmune gastritis 21,23,24.…”
Section: Discussionmentioning
confidence: 99%
“…The accurate diagnosis of the gastric type of NADET, especially pyloric gland adenoma seems to be clinically important, since such lesions have been shown to be at a high risk of higher grade of dysplasia or adenocarcinoma [14]. Previous studies reported that 30–39% of pyloric gland adenomas contained high-grade dysplasia, and 12% of the tumors were associated with adenocarcinoma [24, 25]. More recently, Matsubara et al [26] demonstrated that pyloric gland adenomas in the stomach and in the duodenum were associated with mutations of a distinctive tumor-suppressor gene referred to as GNAS .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the present case was positive for PAS, differentiated from PGA [16,18]. The dysplastic glands were, however, less reactive to PAS than the surrounding hyperplastic ones, which suggests that the former fairly lost the feature of the original BG to acquire the neoplastic characteristics, such as positivity for MUC5AC.…”
Section: Discussionmentioning
confidence: 87%
“…Some authors insist that PGA is differentiated from BGs [16,17] or BGA [18] on the grounds that, while the former not only expresses MUC6 but MUC5AC, the latter group is stained negative for MUC5AC, but it is the neoplastic BGs that showed positivity for a foveolar mucin marker in the present case, which expressed neither pepsinogen1 nor H + K + -ATPase [3,19]. In addition, the present case was positive for PAS, differentiated from PGA [16,18].…”
Section: Discussionmentioning
confidence: 99%